Efektivitas Sport Education Model Dalam Kurikulum Merdeka Terhadap Pengetahuan Permainan Sepak Bola Siswa Sekolah Menengah Pertama - Agiet Fadilah Rachman; Ega Trisna Rahayu (Journal on Education, 2023)
The shooting technique is a hard kick with the aim of scoring goals in a soccer game called shooting or shooting. The basic skill that must be possessed by a soccer player to be developed in order to be able to score a goal kick is to kick hard and accurately. Controlling technique is an attempt to stop the ball that is going fast when playing soccer. Many learning methods in schools are used by teachers when learning. This can help students improve their ability to master the basic techniques of soccer, but in field practice there are still many students who do not master the modules that are informed by the teacher and cannot reach their learning outcomes. By using the sports education model of education, students are expected to be more enthusiastic and active, because using the right method gives a pleasant impression and students will find it easier to talk with their friends. The purpose of this research is to find out how useful the Sport Education Model in the Independent Curriculum is on Knowledge of the Game of Football for SMP 268 Jakarta students. The research uses a quantitative approach to experimental procedures with a one group pre-test post-test design. There are also those who are the population in this research, namely students of SMP 268 Jakarta. The sample in this research was students of class VII G, totaling 32 students. The results of the hypothesis test using the t-test It is known that the value of Sig. (2-tailed) of 0.000 <0.05, it can be concluded that there is a significant difference between the results of the pre-test and post-test. In learning the basic technique of passing football to students it is acceptable. The peer teaching learning model is declared effective because the overall N-Gain average score in the N-Gain improvement test is 0.56, or the increase is in the effective category.